OPTIMASI JARAK PEMASANGAN SOLID RIVET TERHADAP KEKUATAN HORIZONTAL STABILIZER PADA PESAWAT N 219 - Selvira Ayunda Rahma (2023)
The N 219 aircraft is a type of aircraft produced by one of the state-owned aircraft industry in Indonesia which is conducting research to make aircraft that have efficiency to deal with Indonesia's natural conditions. Besides that, it is expected to be able to carry passengers and cargo in large numbers. This research is focused on optimizing the distance for installing solid rivets on the horizontal stabilizer of aircraft N 219. The material used is Aluminum plate type QQ-A-250 while the solid rivets use Aluminum 2117 material which is given a variation of the distance and diameter of the solid rivets. The study carried out a load of one rib of 55000 N with variations in diameter of 3.2 mm and 4 mm and variations in spacing of 17.6 mm and 22 mm. The simulation results on a diameter of 3.2 mm with a distance of 17.6 mm produce a maximum stress of 237.8 MPa with a displacement of 1.573 mm and a safety factor of 1.16. Meanwhile, the diameter of 4 mm with a distance of 22 mm produces a maximum stress of 100.6 MPa with a displacement of 1.416 mm and a safety factor of 2.73. Therefore the most optimal distance and diameter for installing solid rivets on the horizontal stabilizer of the N 219 aircraft are solid rivets with a head diameter of 4 mm and a distance of 22 mm.